2013
DOI: 10.1016/j.clinph.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Persons with Parkinson’s disease exhibit decreased neuromuscular complexity during gait

Abstract: Objective Individual muscle activation patterns may be controlled by motor modules constructed by the central nervous system to simplify motor control. This study compared modular control of gait between persons with Parkinson’s disease (PD) and neurologically-healthy older adults (HOA) and investigated relationships between modular organization and gait parameters in persons with PD. Methods Fifteen persons with idiopathic PD and fourteen HOA participated. Electromyographic recordings were made from eight l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
121
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(141 citation statements)
references
References 37 publications
6
121
1
6
Order By: Relevance
“…In fact, we demonstrated that different altered motor behaviors may be constructed by a common set of muscle synergies (as results shown in Figures 7 and 8). Our findings support prior works related to the changes in the modular organization of different motion patterns of healthy and pathological subjects [35,36].…”
Section: Discussionsupporting
confidence: 82%
“…In fact, we demonstrated that different altered motor behaviors may be constructed by a common set of muscle synergies (as results shown in Figures 7 and 8). Our findings support prior works related to the changes in the modular organization of different motion patterns of healthy and pathological subjects [35,36].…”
Section: Discussionsupporting
confidence: 82%
“…Neural control studies have shown that a large number of muscle EMG signals collected during walking can be decomposed into three to six independent time-varying basis signals called "neural commands" [17][18][19][20]. Recent work has also shown that neural commands extracted from a subset of experimentally measured EMG signals can reconstruct the shapes of the omitted EMG signals accurately [21].…”
Section: Introductionmentioning
confidence: 99%
“…Devido aos comprometimentos motores que os indivíduos com DP apresentam, esse grupo encontra-se mais vulnerável a sofrer acidentes de transito [5] visto que esses déficts motores podem gerar modificações nos padrões da marcha, as quais dificultam sua execução de maneira eficiente e segura [6,7].…”
Section: Introductionunclassified